To the Senate and House of Representatives - Allen, William, 1784-1868; McKeen, Joseph, 1787-1865; Story, Joseph, 1779-1845 (Document (Maine. Legislature. Senate), 1834)
Includes copies of proceedings of the Board of Trustees of Bowdoin College concerning a suit brought by Dr. William Allen to recover salary he claims due to him as president of that institution. Also, the text of Judge Story's opinion (pages 9-30) in the case of William Allen vs. Joseph McKeen, treasurer of Bowdoin College.